Regulation and Functions of 15-Lipoxygenases in Human Macrophages - Snodgrass, Ryan G.; Brüne, Bernhard (Frontiers in Pharmacology, 2019)
Lipoxygenases (LOXs) catalyze the stereo-specific peroxidation of polyunsaturated fatty acids (PUFAs) to their corresponding hydroperoxy derivatives. Human macrophages express two arachidonic acid (AA) 15-lipoxygenating enzymes classified as ALOX15 and ALOX15B. ALOX15 which was first described in 1975 has been extensively characterized and its biological functions investigated in a number of cellular systems and animal models. In macrophages ALOX15 functions to generate specific phospholipid (PL) oxidation products crucial for orchestrating the nonimmunogenic removal of apoptotic cells (ACs) as well as synthesizing precursor lipids required for production of specialized pro-resolving mediators (SPMs) that facilitate inflammation resolution. The discovery of ALOX15B in 1997 was followed by comprehensive analyses of its structural properties and reaction specificities with PUFA substrates. Although its enzymatic properties are well described, the biological functions of ALOX15B are not fully understood. In contrast to ALOX15 whose expression in human monocyte-derived macrophages is strictly dependent on Th2 cytokines IL-4 and IL-13, ALOX15B is constitutively expressed. This review aims to summarize the current knowledge on the regulation and functions of ALOX15 and ALOX15B in human macrophages.